L’étrange étranger: l’avenir incertain de l’immigration canadienne - Janik, Kinga (Refuge: Canada’s Journal on Refugees, 2004)
This article aims at presenting a reflection on the place to be accorded to refugees in the Canadian society, while at the same time being mindful of security considerations. The fear of new terrorist attacks has prompted North American governments to look inwards and has exacerbated negative feelings towards foreigners. This feeling weighs heavily against refugees. The confusion surrounding what categories of people are trying to cross the Canadian border renders even more insecure the fate of refugees who are seeking asylum in Canada through legitimate ways. This article deals mainly with the way certain government initiatives cast a negative light on refugees. More specifically, the author questions the direction taken by the new government that came into power on 12 December 2003, including the setting up of an agency for border services similar to the US Home Security agency.